Neighborhood Attributes Associated With the Social Environment - Child, Stephanie T.; Schoffman, Danielle E.; Kaczynski, Andrew T.; Forthofer, Melinda; Wilcox, Sara; Baruth, Meghan (American journal of health promotion, 2016)
Purpose. To examine the association between specific attributes of neighborhood environments and four social environment measures. Design. Data were collected as part of a baseline survey among participants enrolling in a walking intervention. Setting. Participants were recruited from a metropolitan area in a Southeastern state. Subjects. Participants (n = 294) were predominantly African-American (67%) and female (86%), with some college education (79%) and a mean age of 49. Measures. The International Physical Activity Questionnaire Environment Module assessed perceptions about neighborhood attributes. The social environment was assessed using three distinct scales: social cohesion, social interactions with neighbors, and social support for physical activity from family and friends. Analysis. Multiple regression models examined associations between neighborhood attributes and social environment measures, adjusting for demographic variables. Results. Having walkable destinations and having access to amenities and transit stops were associated with increased interactions with neighbors (b = 1.32, 1.04, and 1.68, respectively, p < .05). Attributes related to structural support for physical activity (sidewalks, street connectivity, recreation facilities) were associated with increased interactions with neighbors (b = 1.47, 1.34, and 1.13, respectively, p < .05). Bicycling facilities that were maintained (i.e., bike lanes, racks) were associated with social support for physical activity from family and friends (b = .43 and .30, respectively, p < .05). Conclusion. The study highlights key attributes of neighborhood environments that may be associated with the social context of such settings.